RESEARCH OF THE CHANGE OF THE MOTION MODES OF THE WORKING ARRAY IN A TURNING MACHINE WITH AN ADDITIONAL MOVEABLE SLIDING LINK DEPENDING ON THE CHANGE OF DESIGN FEATURES - ZALYUBOVSKYI, Mark; PANASYUK, Igor; LYCHOV, Dmitro; KOSHEL, Ganna (Herald of Khmelnytskyi National University. Technical sciences, 2023)
With the help of the SolidWorks automated design system, analytical studies of the rolling machine with complex spatial movement of the working capacity of the "Turbula" type, which contains an additional moving link of the slider in its kinematic chain, were performed. On the basis of the analytical studies, the relationship between the change in the modes of movement of the working array in the middle of the container, the value of the angular velocity of the drive shaft, the scale standard size and the ratio of the interaxial distance of the container to the interaxial distance of the forks was determined. The classification of the movement modes of the working massif is presented, in particular, which should include cascade, mixed and waterfall movement modes. Each movement mode corresponds to the implementation of the corresponding types of felting technological operations or mixing of loose fine-dispersed substances. The effect of changing the length of the working capacity, which is characterized by the ratio of the interaxial distance of the working capacity to the interaxial distance of the leading or driven forks of the machine, on the change in the modes of movement of the working array has been established. Mathematical dependencies have been obtained for determining the maximum angular velocity of the drive shaft of the "Turbula" type rolling machine with an additional movable slider link, which will correspond to the formation of the necessary mode of movement of the working array. The presented results of analytical studies can be applied in the relevant design bureaus of machine-building enterprises at the stage of designing equipment with complex spatial movement of working capacities and felting technological processes.
Keywords: additional moving link; slider; working array; felting